Tuna Keleştemur G ., Tatlı Seven P., Yılmaz S.2012. Effects of Dietary Propolis and Vitamin E on Growth Performance and Antioxidant Status in Blood of Juvenıle Rainbow Trout (Oncorhynchus mykiss) Under Different Flow Rates. Zoologia , - Tuna Keleştemur, Gülüzar, Pınar, Seval Tatlı Seven, Yılmaz; Tuna Keleştemur G., Tatlı Seven P., Yılmaz S. (My University, 2012)
The present study investigated the effects of propolis and vitamin E supplementation in diets of juvenil rainbow trout subjected to two different flow rates with or without flow stress (0.9 and 2.1 l/min, respectively) on final weigth (FW), condition factor (CF), feed conservation ratio (FCR), protein efficiency ratio (PER) and vitamin A, C and E concentrations and malondialdehyde (MDA) levels in serum as well as plasma superoxide dismutase (SOD) activity. The experimental groups were as follows: group C was fed a basal diet, group P10 was fed a basal diet supplemented with 10 g propolis/kg, group P30 was fed a basal diet supplemented with 30 g propolis/kg, group E60 was fed a basal diet supplemented with 60 mg vitamin E/kg. CF and PER were not different among all diets groups for both flow rate treatments (p > 0.05). The FCR improved in P10, P30 and E60 diet groups compared to C diet group at 2.1 l/min flow rate (p < 0.05). The FCR of E60 and P30 were found to be better than C and P10 diet groups at 0.9 l/min flow rate (p < 0.05). Vitamin E and propolis supplementations did not affect vitamin A concentration of serum for either flow rate (p > 0.05). Fish fed with diet E60 had higher serum vitamin E concentration than other groups (p < 0.05). Serum Vitamin C concentration was only affected by the propolis supplemented diets. MDA level of E60 group was found significantly lower comperad to other groups for both flow rate (p < 0.05). Plasma SOD activity significantly decreased in the E60 group compared to other groups at 2.1 l/min flow rate (p < 0.05). But plasma SOD activity was not different among all diets groups at 0.9 l/min flow rate (p > 0.05). KEY WORDS. Lipid peroxidation; rainbow trout; superoxide dismutase; vitamin E.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Lipid peroxidation; rainbow trout; superoxide dismutase; vitamin E.